2010
DOI: 10.1039/c0dt00807a
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturation and variable hapticity in binuclear azulene manganese carbonyl complexes

Abstract: Azulene is reported to react with Mn(2)(CO)(10) to give trans-C(10)H(8)Mn(2)(CO)(6), which has been shown by X-ray crystallography to have a bis(pentahapto) structure with no metal-metal bond. This structure is found by density functional theory to be the lowest energy C(10)H(8)Mn(2)(CO)(6) structure. However, a corresponding bis(pentahapto) cis-C(10)H(8)Mn(2)(CO)(6) structure, also without an Mn···Mn bond, lies within ~1 kcal mol(-1) of this global minimum. The lowest energy C(10)H(8)Mn(2)(CO)(5) structure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…BP86 predictions for the azulene series (C 10 H 8 )Mn 2 (CO) n (n = 5, 4, 3, and 2) 319 show mainly η 5 ,η 5 -coordination modes for the bicyclic ligand, except for two triplet minima (Table 18). The (C 10 H 8 )Mn 2 (CO) 5 system 09 has two singlet minima with The remaining results of this subsection are compiled from computational (BP86) results where some consistent trends are discernible in Tables 16 to 18 for various series of binuclear manganese carbonyl complexes.…”
Section: Binuclear Manganese Carbonyl Complexes With Carbocyclic Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…BP86 predictions for the azulene series (C 10 H 8 )Mn 2 (CO) n (n = 5, 4, 3, and 2) 319 show mainly η 5 ,η 5 -coordination modes for the bicyclic ligand, except for two triplet minima (Table 18). The (C 10 H 8 )Mn 2 (CO) 5 system 09 has two singlet minima with The remaining results of this subsection are compiled from computational (BP86) results where some consistent trends are discernible in Tables 16 to 18 for various series of binuclear manganese carbonyl complexes.…”
Section: Binuclear Manganese Carbonyl Complexes With Carbocyclic Ligandsmentioning
confidence: 99%
“…BP86 predictions for the azulene series (C 10 H 8 )­Mn 2 (CO) n ( n = 5, 4, 3, and 2) show mainly η 5 ,η 5 -coordination modes for the bicyclic ligand, except for two triplet minima (Table ). The (C 10 H 8 )­Mn 2 (CO) 5 system 09 has two singlet minima with long Mn–Mn single bonds of lengths 3.025 and 2.969 Å.…”
Section: Manganese–manganese Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…In binuclear azulene metal carbonyls the five-membered ring is almost always bonded to a metal atom as a pentahapto ligand as shown by both experimental [1] and theoretical [11,12] studies. However, the hapticity of the azulene seven-membered ring is variable as shown by both experimental and theoretical studies.…”
Section: Introductionmentioning
confidence: 95%
“…The metal centre can bond to both rings simultaneously, forming η 5 + 1 , η 5 + 2 and η 7 + 2 bonds. [15,[34][35][36][37] Korichi et al have reported the relative energy of the isomers of several mononuclear Az complexes. Their results do not show a clear trend on the preference of the metal for one of the two rings.…”
Section: Introductionmentioning
confidence: 99%